Effectiveness of Physical Therapy in the Recovery of Patients with Musculoskeletal Injuries: A Longitudinal Study - Carmen María Delgado Vilela; Marlon Miller Neira Pacherres; David Marcelo Guevara Hernández (International Journal of Medical Toxicology and Legal Medicine, 2024)
Physiotherapy is a fundamental intervention in the recovery of patients with musculoskeletal injuries, allowing the restoration of functionality and the reduction of pain. This longitudinal study examines the effectiveness of a physiotherapy program in a group of patients with various musculoskeletal injuries, assessing their progress over a six-month period. Functional recovery, pain reduction, and quality of life were analyzed, demonstrating that physical therapy is effective in improving symptoms and long-term functionality. The findings suggest the importance of an individualized and prolonged approach to optimize outcomes in musculoskeletal rehabilitation.